6x-7+4x+3(2)=(3.75+4.5)4+2x+2

Simple and best practice solution for 6x-7+4x+3(2)=(3.75+4.5)4+2x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-7+4x+3(2)=(3.75+4.5)4+2x+2 equation:



6x-7+4x+3(2)=(3.75+4.5)4+2x+2
We move all terms to the left:
6x-7+4x+3(2)-((3.75+4.5)4+2x+2)=0
We add all the numbers together, and all the variables
6x+4x-((8.25)4+2x+2)-7+32=0
We add all the numbers together, and all the variables
10x-((8.25)4+2x+2)+25=0
We calculate terms in parentheses: -((8.25)4+2x+2), so:
(8.25)4+2x+2
determiningTheFunctionDomain 2x+2+(8.25)4
We add all the numbers together, and all the variables
2x+35
Back to the equation:
-(2x+35)
We get rid of parentheses
10x-2x-35+25=0
We add all the numbers together, and all the variables
8x-10=0
We move all terms containing x to the left, all other terms to the right
8x=10
x=10/8
x=1+1/4

See similar equations:

| -3(8k+5)=3 | | -3(8k=5 | | -13n-40=-170 | | 8+2/5m=4 | | 5t-10=-5t-90 | | 8b=5.5 | | -.5x=-14 | | -10y-75+4y=3 | | (360-244)-(23)=b | | n=6-4(n) | | -2x+-5=-15 | | 20=-6t-4 | | 3(2x+8)=14x-4(3x-6) | | 15x^2/9=143 | | n+43=10 | | 25=u-2-14 | | -1=r-3/8 | | 1/2x-4=2/3x-8 | | 3x-24=4x-46 | | 2x-840=1000 | | 180-(92+78)=x | | 1/3(9k+13)=15 | | 2y+3(y+4)=13 | | 7(×-5)=x+13 | | 15x-80=75 | | 2.5(x+4)+x=38 | | 9/10=5/10v | | (x+5)=(x+13) | | 3(8+e)=21 | | 180=4x+3x+5+8x-14 | | 2a-7=-a-10 | | -4n=-7n(1-2n) |

Equations solver categories